(untitled) (Książnica Śląska, 2025)
In 2023, the Silesian Library received a collection of photographs by the Polish artist photographer Stanisław Michalski as a gift. The article discusses this vast collection (426 pictures) with portrait, sociological and documentary themes. The collection includes series presenting the everyday life of the Roma and student communities, as well as photographs documenting the disappearing rural landscape and detail shots captured in urban space. The text underlines Stanisław Michalski’s creative attitude, his way of perception and working methods, and places him against the background of the achievements of other Polish and foreign photographers. The author of the article describes also the artist’s latest area of interest, expressed in works from the Symetria serie and his own special technique – reanigrafia.